MODERN APPROACHES TO THE EDUCATIONAL SYSTEM OF PRESCHOOL ORGANIZATIONS - Nazirova Guzal Malikovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article is devoted to substantiation of a new paradigm of preschool education, based on the heuristic possibilities of the concept of functional asymmetry of human brain being a system-forming factor for building a new paradigm of education.